2017
DOI: 10.1186/s13287-016-0461-6
|View full text |Cite
|
Sign up to set email alerts
|

Determinates of muscle precursor cell therapy efficacy in a nonhuman primate model of intrinsic urinary sphincter deficiency

Abstract: BackgroundCell therapy for intrinsic urinary sphincter deficiency (ISD) in women has been moderately effective, and improvements are needed. To improve treatment efficacy, it is important to better understand determinates of cell efficacy in the different patient cohorts. We have reported that in nonhuman primates the chronicity of ISD may affect cell efficacy, but additional factors (age, psychosocial stress, hormone status, body weight) can be associated with many disease/treatment outcomes in women – and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
175
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(181 citation statements)
references
References 20 publications
6
175
0
Order By: Relevance
“…For example, one group reported that the therapeutic effect of MSC-exosomes in an OA animal model is a result of exosomes enhancing synthesis and suppressing the degradation of the chondrocyte extracellular matrix (ECM). This was confirmed via an in vitro investigation on chondrocytes treated with the proinflammatory cytokine interleukin (IL)-1β, where exosomes increased collagen type II synthesis and decreased the expression of ADAMTS5, an ECM degrading enzyme [ 74 ]. A second study reported that MSC-exosomes protected OA mice from joint damage by inducing chondroprotective actions.…”
Section: Clinical Applicationsmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, one group reported that the therapeutic effect of MSC-exosomes in an OA animal model is a result of exosomes enhancing synthesis and suppressing the degradation of the chondrocyte extracellular matrix (ECM). This was confirmed via an in vitro investigation on chondrocytes treated with the proinflammatory cytokine interleukin (IL)-1β, where exosomes increased collagen type II synthesis and decreased the expression of ADAMTS5, an ECM degrading enzyme [ 74 ]. A second study reported that MSC-exosomes protected OA mice from joint damage by inducing chondroprotective actions.…”
Section: Clinical Applicationsmentioning
confidence: 92%
“…In which, inflammation within the synovial capsule causes a loss of articular cartilage which in turn leads to joint degeneration, and sclerotic changes to the surrounding bone tissue [ 72 ]. Studies have shown that MSC-exosomes induce healing by promoting chondrocytes proliferation and migration, which leads to cartilage regeneration and the protection of the underling bone tissue [ 73 ]. Another reported exosomal action that is crucial in OA management is restoring the synovial homeostasis, which is essential for tissue healing and repair.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Various approaches using cellular and biochemical components have been explored in vitro and in vivo to enhance the regenerative capacity of injured skeletal muscle and peripheral nerves. Among them, stem cell-based therapies have clear beneficial effects on skeletal muscle and peripheral nerve repair [32,33]. Although the mechanisms by which stem cell therapy act are still unknown, recent evidence has suggested they might be related to long-distance cell-to-cell communication via secreted paracrine factors in the extracellular environment [34].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic low back pain (LBP) is the leading cause of disability worldwide and the social and economic impact is enormous [ 1 ]. Not all degenerated discs exhibit chronic LBP, however, intravertebral disc (IVD) degeneration is considered as a major cause of chronic LBP [ 1 , 2 , 3 , 4 ]. IVD degeneration is a complex and multifactorial process, influenced by genetic, nutritional, and mechanical factors [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…These molecules can be produced by both IVD cells and immune cells, such as macrophages [ 6 ], and are known to be associated with discogenic back pain [ 6 ]. IVD degeneration is characterized by the loss of IVD cells and extracellular matrix (ECM) such as aggrecan and collagen type II, with the upregulation of matrix metalloproteinases (MMPs) and inflammatory mediators leading to progressive and irreversible damage of IVD structure [ 1 , 3 , 4 , 6 , 7 , 8 ]. Eventually, IVD degeneration can lead to the onset of additional spinal conditions, including disc herniation, spinal stenosis, facet joint osteoarthritis, and spondylolisthesis [ 1 , 3 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%